Comments on Canadian proposal for changes in WMO sea ice terminology - Armstrong, Terence; Roberts, Brian; Swithinbank, Charles (Polar Record, 1965)
The Canadian proposals outlined by Miss Dunbar ( antea , p 717–22) have the great advantage of having grown out of several years' practical application of the WMO International Ice Nomenclature. The proposals are made not only out of a desire to refine concepts and lessen ambiguity as knowledge grows, but also out of a need for reorganization called for by practical considerations. This is the right way for a terminology to develop.